Mind = Blown : Amazing Facts About This Weird, Hilarious, Insane World - Santoro, Matthew and Greene, Jake (U.K. Viking, an imprint of Penguin Books, 2016)
Matthew Santoro's originality and humor has attracted millions of fans, making him a beloved YouTube star. His weekly videos on amazing and little-known facts are eagerly anticipated by his many subscribers and followers around the world. In his first-ever book, Matthew's love of weird and wacky knowledge explodes with new facts and stories from around the planet, and beyond. Surprising, and always entertaining, Mind = Blown offers even more of Matthew's unique take on this hilarious, crazy world.
Include Index and Notes and Illustration
Keywords: Curiosities and wonders -- Questions and answers